A Retrospective Cohort Study of Hospital Versus Home Care for Pregnant Women With Preterm Prelabor Rupture of Membranes. Issue 11 (November 2017) - Palmer, Lynne; Grabowska, Kirsten; Burrows, Jason; Rowe, Hilary; Billing, Erin; Metcalfe, Amy
Abstract : (Abstracted from Int J Gynecol Obstet 2017;137:180–184) Pregnancies with preterm prelabor rupture of membranes (PPROM) are at risk of preterm labor, and further risks of infection or adverse cord or placental events increase perinatal morbidity and mortality. Monitoring pregnancies with PPROM in the hospital setting until at least 34 weeks is the standard practice to prevent prematurity-related complications.